2012
DOI: 10.1002/cphc.201200218
|View full text |Cite|
|
Sign up to set email alerts
|

Photophysical and Electrochemical Properties, and Molecular Structures of Organic Dyes for Dye‐Sensitized Solar Cells

Abstract: The authors have noticed an error in the structure of compound PS-1 in Scheme 1 of their Review. The corrected version of PS-1 is presented below. The authors apologize for this error and for any inconvenience caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
224
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(234 citation statements)
references
References 578 publications
3
224
0
1
Order By: Relevance
“…The LUMO levels of sensitizers must be located slightly above the energy levels of semiconductors so that sensitizers can inject electrons into the conduction band of TiO 2 with high quantum yields [24]. Ooyama and Harima [25] reported that the desire difference of LUMO level of sensitizer and CB of TiO 2 should be more than 0.2 eV. Even though the LUMO levels of all investigated sensitizers were found to be more than 0.2 eV, this condition should be followed with efficient dye regeneration by electron transfer from the redox couple in the electrolyte to obtain high efficiency device.…”
Section: Optical Band Gap and Homo-lumo Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LUMO levels of sensitizers must be located slightly above the energy levels of semiconductors so that sensitizers can inject electrons into the conduction band of TiO 2 with high quantum yields [24]. Ooyama and Harima [25] reported that the desire difference of LUMO level of sensitizer and CB of TiO 2 should be more than 0.2 eV. Even though the LUMO levels of all investigated sensitizers were found to be more than 0.2 eV, this condition should be followed with efficient dye regeneration by electron transfer from the redox couple in the electrolyte to obtain high efficiency device.…”
Section: Optical Band Gap and Homo-lumo Calculationsmentioning
confidence: 99%
“…The energy conversion efficiency (n) of the mixed sensitizers was higher because of the value of J sc is higher than that of the individual sensitizers. The value of J sc indicates strong interaction of TiO 2 with sensitizer in photoanode and their capability to absorb light that lead to high electron-injection efficiency [25,29,30]. Figure 9 shows the IPCE spectra of all of the investigated sensitizers.…”
Section: Optical Band Gap and Homo-lumo Calculationsmentioning
confidence: 99%
“…However, it was emphasized in a recent review by Ooyama and Harima that, the energy difference between these levels should be at least 0.2-0.3 eV for an efficient electron regeneration. 13 In our molecules, these were 0.2 and 0.12 eV for TB6 and TB7, respectively. Although, these values seem to be appropriate, a larger gap would be better suited.…”
Section: Njc Papermentioning
confidence: 57%
“…Different classes of molecules can be employed, and among them metal-free organic dyes have been found suitable to ensure efficient light-harvesting, due to their easily tunable structures and photophysical properties, good stability and high molar extinction coefficients [9]. Indeed, a multitude of organic dyes have been already prepared and tested in DSSCs [10,11], most of them sharing the same D-π-A architecture, characterized by electron-donating (D) and electron-accepting (A) groups linked by π-conjugated bridges.…”
Section: Introductionmentioning
confidence: 99%